Prevalência da asma em regiões do Município do Rio de Janeiro - Márcia Garcia Alves Galvão; Marilene A.R. Crispino Santos; Francisco Charles Souza Carvalho; Henrique Pazos F. Martins; Jade Cecílio B. Sampaio; Gabriel Miranda Barbosa (Residência Pediátrica)
INTRODUCTION: Asthma is the most common chronic disease in childhood. In Brazil, the prevalence of active asthma is high. However, it is known that within the same country this prevalence can vary. OBJECTIVES: to describe in the studied sample, the prevalence of asthme, active asthma, asthma diagnosed by a physician, nocturnal cough, cough for more than 10 days after a respiratory infection and respiratory manifestations during physical exertion. METHODOLOGY: Cross-sectional prospective study in a convenience sample of a pediatric population attending the Clínica da Família Souza Marques, in Rio de Janeiro, using a simplified questionnaire. RESULTS: 34.3% (62/204) had active asthma. 30.4% (62/204) had already received a medical diagnosis of asthma. Among those with active asthma, 40% (28/70) had never received this diagnosis. 46% (95/204) had nocturnal awakening in the last 12 months, 30.4% (62/204) had other respiratory manifestations with exertion in the last 12 months, and 27% (55/204) coughed for more than 10 days when they had a cold in the last 12 months. CONCLUSION: Asthma is highly prevalent in the evaluated population. Further research is necessary to deepen the study on the evaluation of respiratory symptoms, the communication of the diagnosis to caregivers and to the need to improve clinical recognition, access to diagnostic tests when indicated, and the communication of diagnosis to families.